High prevalence and genomic characteristics of G6P[1] Bovine Rotavirus A in yak in China. (19th July 2020) - Yan, Nan; Li, Ran; Wang, Yuanwei; Zhang, Bin; Yue, Hua; Tang, Cheng
Abstract : Yak is an iconic species of the Qinghai–Tibet Plateau, which is the world's highest plateau. Here, a total of 541 yak diarrhoeic samples were collected from 69 farms in four provinces in the Qinghai–Tibet Plateau from April 2015 to June 2018, and 73.6 % of samples were detected as Bovine Rotavirus A (BRVA) positive by RT-PCR assay. Two G genotypes (G6, G10) and two P genotypes (P[1], P[11]) were determined, in which G6P[1] BRVA was the predominant strain. Moreover, VP7 and VP4 of these G6P[1] strains showed unique amino acid mutations, such that they clustered into an independent branch in the phylogenetic tree. A strain of BRVA designated as RVA/Yak-tc/CHN/QH-1/2015/G6P[1] was isolated successfully using MA104 cells, and the virus titre was determined as 10 5.84 TCID50 ml –1 . The genome of strain QH-1 had a G6-P[1]-I2-R2-C2-M2-A3-N3-T6-E2-H3 genotype constellation. QH-1 was identified as a reassortment strain of BRVA, human RVA and ovine RVA based on the nucleotide identity and phylogenetic tree of 11 gene segments, indicating its public health significance. To the best of our knowledge, this is the first report on the molecular prevalence and genome characteristics of BRVA in yak, contributing to further understanding of the epidemic and genetic evolution of BRVA.